Experimental Analysis of High Temperature PEEK Materials on 3D Printing Test - Sun Xiaoyong; Cao Liangcheng; Ma Honglin; Gao Peng; Bai Zhanwei; Li Cheng (International Conference on Measuring Technology and Mechatronics Automation (Print), 2017)
As a kind of semi crystalline thermoplastic engineering plastics, Polyetheretherketone (PEEK) has excellent mechanical properties and chemical stability. Aiming at the high temperature properties of PEEK, test and analysis of PEEK fused 3D printing performance was carried out by the fused deposition modeling(FDM), the experimental research date has been obtained by the effect of temperature on the mechanical properties and forming precision, the sheet forming. The result shows that adjusting the hot bed temperature, ambient temperature and filling ratio, it can improve the bonding strength, and it ultimately can improve the mechanical properties and the printing precision of PEEK. Compared to the PLA material, the maximum tensile strength of PEEK reached up to around 77Mpa, which was much larger than the tensile strength of PLA, and has good forming properties in thin layer parts. The analysis of this paper provides an effective basis for the analysis of high temperature 3D material PPEK printing, and provides a new solution for the performance control of high temperature material 3D printing.